1989
DOI: 10.1113/jphysiol.1989.sp017559
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of atrial systole to mitral diastolic blood flow increases during exercise in humans.

Abstract: SUMMARY1. The change in the relative contribution of the early passive and later active phases of transmitral flow to left ventricular filling was studied using Doppler echocardiography in ten normal male subjects during mild exercise.2. The peak velocity of passive flow increased during exercise by a mean of 16 % whereas peak velocity of active flow increased by a mean of 89 %. Hence the ratio of the peak velocities decreased in a linear fashion with a correlation coefficient of r =-095.3. The ratio of the Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Previous studies in humans have demonstrated that the percentage of second-half filling volume increases during supine bicycle exercise (Carroll, Hess, Hirzel & Krayenbuehl, 1983). Additional recent studies with Doppler recordings of transmitral blood flow velocity in normal subjects suggest that the contribution of atrial systole to overall transmitral blood flow progressively increases during mild exercise (Channer & Jones, 1989).…”
Section: Increased Booster Function During Exercisementioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies in humans have demonstrated that the percentage of second-half filling volume increases during supine bicycle exercise (Carroll, Hess, Hirzel & Krayenbuehl, 1983). Additional recent studies with Doppler recordings of transmitral blood flow velocity in normal subjects suggest that the contribution of atrial systole to overall transmitral blood flow progressively increases during mild exercise (Channer & Jones, 1989).…”
Section: Increased Booster Function During Exercisementioning
confidence: 92%
“…Early studies have shown that when atrial fibrillation is converted to sinus rhythm, with little change in ventricular heart rate, there is still a measurable difference in cardiac output, especially during exercise (Hecht, Osher & Samuels, 1951) (Carroll, Hess, Hirzel & Krayenbuehl, 1983). Additional recent studies with Doppler recordings of transmitral blood flow velocity in normal subjects suggest that the contribution of atrial systole to overall transmitral blood flow progressively increases during mild exercise (Channer & Jones, 1989 (Rahimtoola et al 1975), or myocardial hypertrophy (Hanrath, Mathey, Siegert & Bleifeld, 1980 Mechanisms for increased atrial booster function Linden & Mitchell (1960) have shown in anaesthetized open-chest dogs that when LV end-diastolic pressure wVas low, atrial systole caused greater changes in LV fibre length than when LV end-diastolic pressure was high. Doppler echocardiographic measurements have shown the ratio of passive to active transmitral blood flow velocity to be directly related to LV preload (Stoddard, Pearson, Kern, Ratcliff, Arosek & Labovitz, 1989).…”
Section: Increased Booster Function During Exercisementioning
confidence: 96%
“…Several previous studies conducted in vivo have reported a physiological reduction in E/A with increasing HR in healthy subjects (Iliceto et al, 1991; Swinne et al, 1992; Yamamoto et al, 1993). Increasing HR has been correlated to increased atrial systolic velocity (Channer and Jones, 1989; Harrison et al, 1991; Mitchell et al, 1965; Ruskin et al, 1970). However, the functional implication of the elevated role of atrial systole during LV filling under increasing HR is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients with CAD had similar filling characteristics at baseline to controls. Despite the results that may indicate normal or near normal diastolic function, the pseudonormalized pattern caused by the coexistence of approximately equally important abnormalities of chamber stiffness and relaxation may have effected the initial results [17,39,42].…”
Section: Discussionmentioning
confidence: 99%